2020
DOI: 10.26452/ijrps.v11ispl3.3314
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic prescription practice for pulpal pain — An institution-based retrospective study

Abstract: Analgesics are prescribed for various surgical and non-surgical treatments in dentistry; however, they are commonly given for relieving pain. This study is aimed at determining the current analgesic prescription pattern in Chennai to help ascertain that these medications are recommended only when absolutely necessary. The patient records from the Department of Endodontics, Saveetha dental college, Chennai from June 2019-April 2020, and patients who were prescribed analgesics for pulpal pain - pretreatment purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We have found similar findings in other studies by Nagarajan et al 33 the most prescribed periodontal pain medication was paracetamol & aceclofenac. Cinthura et al 34 documented paracetamol alone and paracetamol & aceclofenac most prescribed. Rajaraman et al 35 documented that dentist favoured combination of analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…We have found similar findings in other studies by Nagarajan et al 33 the most prescribed periodontal pain medication was paracetamol & aceclofenac. Cinthura et al 34 documented paracetamol alone and paracetamol & aceclofenac most prescribed. Rajaraman et al 35 documented that dentist favoured combination of analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous findings in India by Nagarajan et al [13] paracetamol/aceclofenac was the most often recommended for periodontal pain treatment. Cinthura et al [14] reported that paracetamol alone and paracetamol/aceclofenac were the most often prescribed analgesics. According to Rajaraman et al [15], dentists preferred combination analgesics.…”
Section: Discussionmentioning
confidence: 99%